Motives and preventive behaviors related to condom use among university students in Ciudad Juárez (Mexico). - Piña López, Julio Alfonso; Lozano Ramírez, Dora Isabel; Vázquez Ramírez, Patricia; Carrillo Saucedo, Irene Carolina (Anales de Psicología / Annals of Psychology, 2010)
A cross-sectional study of psychological variables underlying different sexual behaviors was carried out in Ciudad Juarez, Mexico. The sample consisted of 798 university students from a higher education insti-tution. Participants answered a questionnaire measuring psychological variables underlying preventive and high-risk sexual behaviors related to HIV infection. A multiple regression analysis showed the following re-sults: condom use behavior across an active sexual life was predicted by two types of motives "I used it to avoid a pregnancy" and "I used it to avoid a sexual infection" (F [2, 271] = 14.863; p < .005), while condom use with casual partners was predicted by one motive "I used it to avoid a pregnancy" (F [2, 145] = 0.957; p < .005). Because motives underlying condom use behaviors are different, prevention programs need to recong-nize these motives and their influential role in the processes of competen-cies training, aimed at promoting the efficient practice of preventive be-haviors.